THE EFFECT OF CHARITY ACTIVITIES ON STREET ON TRAFFIC FLOW CHARACTERISTICS ON THE TRANS KALIMANTAN ROAD SECTION OF BARITO KUALA REGENCY - Jiani, Harjianti Shinta Rosalia; Radam, Iphan F. (Universitas Lambung Mangkurat, 2024)
The location reviewed in this study is on Jalan Trans Kalimantan KM.12 Barito Kuala Regency precisely in front of the entrance direction of GIBS Junior High School, which is influenced by charity activities. This causes increased density and decreased vehicle speed, making the speed of vehicle movement slow. Therefore, it is necessary to conduct research to find out how much influence it causes. What will be analyzed is both directions because they are equally affected by charity activities with conditions when there are charity activities and when there are no charity activities, requiring data in the form of LHR data and the speed taken directly at the research site. To find out these influences used conventional methods (Greenshield, Greenberg, and Underwood). From the results of the analysis, the model selected affected by charity in the direction on Handilbakti and the direction on Marabahan is the Greenshield model, and the model selected when it is not affected by charitable donations in the direction on Handilbakti and the direction of Marabahan is the Greenshield model, In each direction from the calculation results with conditions when there is a charity activities there is a maximum volume decrease of 18.53% from the Handilbakti direction, and from the Marabahan direction by 40.26%. The maximum speed in the Handilbakti and Marabahan directions has decreased by 59.71% and 61.40%, and for maximum density in the Handilbakti and Marabahan directions there has been an increase of 30.11% and 15.07%. LOS got from a degree of saturation > 0.8 when there was a charity activities in the direction at Handilbakti which occurred between 16.00 s.d. 18.00 WITA, and the direction of Marabahan occurs in the range of 15.10 – 16.40 WITA and the range of 16.30 – 18.00 WITA. Meanwhile, LOS when there is no charity in the direction of Handilbakti and Marabahan dominantly shows B level (66%) and C level (79%). Keywords: Charity Activities on Street, Level of Service, Traffic Characteristics